Telemedicine: Blood Pressure Monitoring System for Individual Use through Internet - Elobeid, Wagle Allah Ahmed (2000)
Hypertension and Hypotension are common diseases in Malaysians and the world at large. If not treated, they predispose the patient to more serious conditions like coronary heart disease and stroke. Regular blood pressure monitoring at home can be helpful in the management of the diseases. Doctors can use the data to evaluate the patient's condition and institute treatment. In this project, an Internet-based Blood Pressure Monitoring System (IBPMS) was developed, as a new application in telemedicine, for monitoring the patient's blood pressure at home. The data is automatically sent to the hospital database via the Internet. This system consisted of both hardware and software. A serial interface card connected to a blood pressure device was designed and tested. The software, which included a graphical display of blood pressure and homepage, was developed. The IBPMS system was designed and tested. The software, Visual Designer, was used to create the system, graphical display and control the operation of the interface card, while Hyper Text Mark-up Language (HTML) was used to develop the homepage. The complete IBPMS has been designed and experimentally tested with four subjects of ages from 25 to 30 years old. The measurement has been taken under the required room temperature and proper setting. Then these results have been compared with the real readings by using Omron blood pressure monitoring device. The difference is found to be within the range of the standard error. Thus, it can be stated that the developed IBPMS system is a convenient tool to patients for regular blood pressure monitoring at home and an important and useful application to the telemedicine service.